2015
DOI: 10.1063/1.4926661
|View full text |Cite
|
Sign up to set email alerts
|

Formation of shallow boron emitters in crystalline silicon using flash lamp annealing: Role of excess silicon interstitials

Abstract: This thesis explores various processing and materials aspects of an oxide solar cell. A tandem structure consisting of a Silicon (Si) bottom cell, and a Cuprous Oxide (Cu 2 O)/Zinc Oxide (ZnO) top cell is suggested, and several materials challenges relevant for the design is addressed. Using Flash Lamp Annealing, shallow p-type emitters are produced in Si by indiffusion of Boron (B) from a surface source. The B diffusion is shown to be enhanced by a transient of Si interstitials originating from the surface co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 129 publications
0
2
0
Order By: Relevance
“…Moreover, Normann et al and Riise et al investigated the in-diffusion of phosphorus and boron using spin-on deposition of a phosphorus and boron source, respectively, on the surface of monocrystalline silicon followed by FLA, as a viable method of forming high-concentration shallow emitters for solar cells [101,102]. By varying both the energy density of a 20 ms flash in the range from 62 to 132 J cm −2 and the sample preheating, it was observed that FLA treatments can in-diffuse a high concentration of phosphorus atoms that become electrically active.…”
Section: Shallow Junctionsmentioning
confidence: 99%
“…Moreover, Normann et al and Riise et al investigated the in-diffusion of phosphorus and boron using spin-on deposition of a phosphorus and boron source, respectively, on the surface of monocrystalline silicon followed by FLA, as a viable method of forming high-concentration shallow emitters for solar cells [101,102]. By varying both the energy density of a 20 ms flash in the range from 62 to 132 J cm −2 and the sample preheating, it was observed that FLA treatments can in-diffuse a high concentration of phosphorus atoms that become electrically active.…”
Section: Shallow Junctionsmentioning
confidence: 99%
“…Annealing technique is another hot topic in the research of ultra-shallow doping. The desire to maximize dopant activation with minimized diffusion in USJ fabrication has reignited the research interests in subsecond annealing techniques such as FLA [61][62][63][64] and PLA [62,[65][66][67][68][69] that were first proposed in late 1970s [70,71].…”
Section: Ion Implantation and Advanced Annealing Techniquesmentioning
confidence: 99%